Analisis Kemampuan Literasi Sains Mahasiswa Pendidikan Biologi IAIN Ambon - Halifah, Halifah (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2025)
Analysis of students' science literacy skills provides educators with alternatives that can be given to students as an evaluation in learning. This research aims to determine the Science Literacy Skills of Students. This research was conducted in the Odd semester of the 2024/2025 academic year at the State Islamic Institute of Ambon. The subjects of this research were 24 active students of the Biology Education Study Program. The instrument developed was limited to the material on Pests and Diseases of Marine Products. The research method is descriptive statistical analysis by describing the existing conditions without treatment. The instrument developed consisted of eight multiple-choice written test questions. The research revealed that the science literacy ability of Biology Education students at IAIN Ambon is generally still classified as low, with a percentage of (59.47%). The indicator that shows the ability to explain scientific phenomena accurately is in the very low category (37.33%), and the indicator related to data interpretation and drawing conclusions appropriately is in the good category (76.00%). This shows that the science literacy competence of these students needs to be improved through a science literacy-based learning approach.